Defects and supersolidity: effects of annealing and stress on elastic behavior of solid 4He: Твердый гелий - Syshchenko, A.; Day, J.; Beamish, J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Recent measurements showed that solid 4He can decouple from a torsional oscillator below 200 mK anddefects appear to be crucial to this behavior. Helium’s shear modulus increases in the same range, which canbe understood in terms of dislocations pinned by 3He impurities at the lowest temperatures, but mobile above 100 mK. We have measured helium’s pressure and shear modulus to study the effects of annealing and stresses applied at low temperatures. Pressure gradients produced during crystal growth or plastic deformation are greatly reduced by annealing, but only at temperatures close to melting. Annealing does not change the low-temperature modulus but usually raises it at high temperature, as expected if annealing eliminates some dislocations. Large stresses also affect the modulus, but these changes are reversed by heating above 0.5 K, suggesting that defects introduced by stress are easier to anneal than those produced during growth.